Chaotic Image Encryption Based on Boson Sampling. Issue 2 (14th December 2022) - Shi, Jinjing; Zhao, Tongge; Wang, Yizhi; Feng, Yanyan; Wu, Junjie
Abstract: As a fundamental form of information representation, image encryption is a significant research issue in the multimedia era. An image encryption scheme is proposed benefiting from chaotic random behavior characteristics of Boson sampling (BS) probability distribution, where the chaotic random number sequence is used to implement the encryption process including scrambling image pixels and altering the values of pixels. Further, a BS‐based image encryption prototype system is constructed on the programmable silicon photonic processor chip for BS with 5‐mode 2‐photon, which can encrypt 4 × 4 grayscale images. Besides, experiments for encrypting 256 × 256 gray‐scale images with 20‐mode 8‐photon BS are simulated on the StrawberryFields photonic quantum software platform. Numerical analyses demonstrate the proposed scheme has good effectiveness in terms of randomness test, information entropy, histogram, correlation, key space, key sensitivity, and anti‐attack, offering gains in many cryptographic applications. The BS‐based image encryption prototype system extends the application of BS to solve practical problems in addition to proving quantum advantages. Abstract : This work proposes an image encryption scheme benefiting from chaotic random behavior characteristics of Boson sampling (BS) probability distribution. Furthermore, a BS‐based image encryption prototype system is constructed on the programmable silicon photonic processor chip for BS with 5‐mode 2‐photon, which extends the application of BS to solve practical problems in addition to proving quantum advantages.